Penggunaan Digital Signature Untuk Absensi Pada Universitas Muhammadiyah Purworejo - Widatama Krisna; Hamid Jumasa Muhammad; Danti Puspitaningrum (APIC, 2022)
Abstract— The student attendance system carried out at the Muhammadiyah University of Purworejo currently still uses paper for both students and lecturers. The use of this paper allows errors to occur when the lecturer recapitulates student attendance data. In addition, the attendance process that still uses paper is considered less effective and efficient. Therefore, it is necessary to create an information system that can apply digital signatures at the Purworejo Muhammadiyah University to prevent Purworejo Muhammadiyah University students outside of lectures or being absent from being able to fill attendance. With this system, it is hoped that this digital signature can be used in academic information systems and support online learning